CYBERSECURITY GOVERNANCE IN PUBLIC INSTITUTIONS: MANAGING DIGITAL RISKS AND RESILIENCE - Desi Rahma Aryanti (Alqaprint Jatinangor, 2025)
This study explores the evolving landscape of cybersecurity governance in public institutions through a comprehensive literature review, emphasizing the management of digital risks and the cultivation of organizational resilience. As public sectors increasingly rely on digital infrastructure, vulnerabilities to cyber threats have grown, necessitating a governance framework that integrates technology, policy, and human factors. The review synthesizes scholarly works published between 2018 and 2025 to identify dominant themes, frameworks, and challenges in public sector cybersecurity. Findings reveal that effective governance requires multidimensional coordination among institutional leadership, regulatory bodies, and information technology systems. Resilience emerges not only from technical preparedness but also from adaptive institutional cultures and proactive policy implementation. The study highlights the critical need for continuous capacity building and strategic policy reform to address emerging digital risks. It further underscores the importance of integrating cybersecurity governance within broader digital transformation agendas. The paper contributes to the theoretical understanding of cybersecurity governance as a vital mechanism for safeguarding public trust and ensuring the sustainability of digital governance systems.